2020
DOI: 10.1302/2633-1462.12.bjo-2019-0004.r1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted total knee arthroplasty demonstrates decreased postoperative pain and opioid usage compared to conventional total knee arthroplasty

Abstract: Aims Robotic-assisted total knee arthroplasty (RA-TKA) has been introduced to provide accurate bone cuts and help achieve the target knee alignment, along with symmetric gap balancing. The purpose of this study was to determine if any early clinical benefits could be realized following TKA using robotic-assisted technology. Methods In all, 140 consecutive patients undergoing RA-TKA and 127 consecutive patients undergoing conventional TKA with minimum six-week follow-up were reviewed. Differences in visual anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 15 publications
2
41
1
1
Order By: Relevance
“…The resultant decreased LOS is beneficial to overall health-care costs associated with the procedure. Our finding of reduced LOS with robotic TKA has been previously shown in a study comparing robotic TKA to manual TKA [ 25 , 31 , 32 ]. These differences in pain scores and opioid usage between patient groups may be attributed to 3 technical differences between RA-TKA and CN-TKA.…”
Section: Discussionsupporting
confidence: 83%
“…The resultant decreased LOS is beneficial to overall health-care costs associated with the procedure. Our finding of reduced LOS with robotic TKA has been previously shown in a study comparing robotic TKA to manual TKA [ 25 , 31 , 32 ]. These differences in pain scores and opioid usage between patient groups may be attributed to 3 technical differences between RA-TKA and CN-TKA.…”
Section: Discussionsupporting
confidence: 83%
“…1 ) [ 12 , 24 , 35 , 42 ]. A list of the 16 studies which met the inclusion criteria are illustrated in Table 1 [ 4 , 18 20 , 23 , 25 , 28 , 30 32 , 36 , 44 , 49 52 ]. Nine studies were identified from Medline and PubMed, and seven additional studies from Google Scholar (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Future well-powered studies should report on the knee alignment and balancing techniques utilised in RATKAs to enable greater comparisons to be made on which techniques maximally benefit patient outcomes and provide better insights into alternate alignment philosophies. Bhimani et al [4] 2020 RATKA: to achieve the desired bone cuts and target limb alignment, along with symmetrically balanced flexion and extension gaps Unknown which technique and which reference alignment was utilised mTKA: A gap balancing technique was utilized using a ligamentous tensioning device with the extension gap balanced followed by balancing the flexion gap after release of the posterior cruciate ligament Gap balancing techniques utilised Kayani et al [18] 2018 mTKA utilised a measured resection technique aligned to the mechanical axis RATKA utilised dynamic referencing to achieve equal gaps throughout the range of motion, utilising gap balancing and kinematic alignment techniques Kayani et al [19] 2018 RATKA: intraoperative dynamic gap balancing techniques were used with kinematic alignment assessed through the arc of motion, and enabled fine tuning of implant positioning based on laxity of the soft tissue envelope, within 2 mm of the planned bone resection Utilised restricted kinematic alignment techniques mTKA: measured resection and mechanical alignment as reference Mahoney et al [28] 2020 Both RATKA and mTKA utilised mechanical alignment as reference for all except nine cases of two centers that were targeted within ± 3 degrees Marchand et al [30] 2017 RATKA: the prosthesis was manipulated allowing for optimal balancing and realignment. The knee was brought into extension, and alignment was checked with the robotic-assisted device both in extension and at 90 degrees of flexion No mention if mechanical/kinematic alignment was utilised to check the knee in extension mTKA: measured resection techniques used with mechanical alignment as reference Smith et al [49] 2019 RATKA: equal gap measurements within 1 mm between the flexion and extension gaps and the medial and lateral gaps, keeping limb alignment within 3 degrees of the mechanical axis and use the bone cuts to balance gaps instead of soft tissue releases unless the target fell out of 3 degrees window, at which point a combination of bone cuts and soft tissue releases was utilized to achieve balanced gaps within 1 mm Restricted kinematic alignment and gap balancing techniques mTKA: Mechanical alignment and measured resection techniques utilised Sultan et al [51] 2019 RATKA: Intraoperative adjustments to the plan were performed to determine ideal component placement for a balanced knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such visual‐ and mechanical‐based methods have been improved to become standard techniques for the past several decades; however, the clinical results of this technique are inherent due to variations in the accuracy of these patterns 14–16 . Recently, a robotic‐assisted TKA technique has been designed and used to improve implantation accuracy 17 . This technique has potentially alleviated the complexity of TKA surgery and has improved both the reproducibility and accuracy of implant positioning 18 .…”
Section: Introductionmentioning
confidence: 99%